If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + 2 = 21 Reorder the terms: 2 + 3b = 21 Solving 2 + 3b = 21 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3b = 21 + -2 Combine like terms: 2 + -2 = 0 0 + 3b = 21 + -2 3b = 21 + -2 Combine like terms: 21 + -2 = 19 3b = 19 Divide each side by '3'. b = 6.333333333 Simplifying b = 6.333333333
| 8n-(2n+7)=29 | | 3k^2+14k-5=0 | | p+2q=10 | | -5(f+7)=3(3f+-1) | | -4(r+3)=-70 | | 3x+5+3x+5+x+x=66 | | 2x-6x+8x-9x= | | (2x+3)(x+5)= | | m^2-28m+25=0 | | 6k-k=27-4 | | 43(x-172)=86 | | 5x^2+34+24=0 | | w^2+17w+16=0 | | 3x+5+x=66 | | 0.20(x+10)+1.40x=66 | | 0.5(8w-6)=17 | | 5(-1.2)-y=4 | | 8w+3=6 | | 3*l=5 | | 4x-6+x=54 | | 5y+1+3y=-5 | | 4=16t-16t^2 | | 9-33=-4z | | -3x-4z=17 | | 5z^2-3x-2=0 | | 3(w-2)=6 | | 2x+3+x=54 | | w-3w=32 | | 2x+3=54 | | 0=-3x^2+2x+5 | | 4x-2(x+5)=-(2x+15) | | 4x-2(x+5)=-(2v+15) |